The Relationship between emotional intelligence and mental health of nursing students at Shahid Beheshti University of Medical Sciences in 2013 - Sima Zohari Anboohi; Seyyed Javad Mosavian; Jamileh Mohtashami; Maliheh Nasiri (Kurdistan University of Medical Sciences, 2016)
Introduction and Aims: considering the nurses health is of paramount importance and it should be taken into account from studentship period. The prevalence of mental disorders in students has been reported from 12.75 to 30.4 percent. Using emotions to enhance cognitive function, appreciation and regulating excitement can help to mental and physical health in different ways. This study aimed to determine the relationship between emotional intelligence and health aspects in the university students of Shahid Beheshti University of Medical Sciences. Matericals and Methods: This descriptive correlational study was conducted on 170 bachelor nursing students. Stratified random sampling method was used. Data were collected using Bar-on emotional intelligence test and 28 question general health questionnaire. Data analysis was conducted using descriptive and inferential statistics (independent t-tests, ANOVA, Pearson correlation and multivariate regression equations of step by step procedure) in SPSS v.20. Results: 75.3 percent of subjects were at good levels of emotional intelligence. The maximum score of emotional intelligence was in interpersonal component and the least average of emotional intelligence was in the compatibility component. Moreover, 70.6 percent were mentally healthy and 28.8 percent were suspected of having mental disorders. Emotional intelligence had a significant inverse relationship with any of the mental health domains, which means that people with higher emotional intelligence had enjoyed less anxiety disorder, social functioning, depression and physical symptoms that are associated with it. Conclusion: considering the results of this study, the development and promotion of nursing students' emotional intelligence can improve their mental health.